Characterization of Addition Porang on Polyacrylamide Polymer for Enhanced Oil Recovery - Siahaya, Jacob; Mardiana, Dwi Atty; Fathaddin, Muhammad Taufiq (Penerbitan Universitas Trisakti, 2023)
The main purpose of polymer injection is to reduce the water-oil mobility ratio. By increasing the viscosity of the injection fluid, polymer injection can increase sweep efficiency, thereby increasing oil recovery. This study aims to determine the viscosity and adsorption effects of adding porang to polyacrylamide polymers. The method used in this research is a laboratory experiment. The salinity of the formation water used in this study was 6000 ppm, 12000 ppm, and 18000 ppm, with variations in polymer concentrations of 2000 ppm, 4000 ppm, and 6000 ppm on the polymer without a mixture of porang and with a mixture of porang. The result of measuring the viscosity of polyacrylamide by adding porang at the salinity of 6000 ppm and polymer concentration of 6000 ppm was 21.82 cp. With the addition of porang to the polyacrylamide polymer at 2000 ppm concentration and 18000 ppm salinity, the adsorption value of the polymer decreased from 2.708 mg/gr to 1.748 mg/gr for 40 mesh sand and from 3.333 mg/g to 2.358 mg/g for 60 mesh sand.